Without a ride in car country – A comparison of carless households in Germany and California. (March 2018) - Kühne, Kathrin; Mitra, Suman K.; Saphores, Jean-Daniel M.
Highlights: We compare carless households in Germany & California, two car-dependent societies. We estimate generalized structural equations models on the 2012 CHTS and 2008 MiD. Educated households are more likely to be voluntarily carless in Germany, not in CA. Employment density has a higher impact in Germany than in CA. To decrease car dependency, CA also needs to adjust the cost of driving. Abstract: One approach to making transportation more sustainable is to transition away from a car-oriented society. Unfortunately, our understanding of the factors that prompt households to voluntarily forgo their motor vehicles is limited. The 2008 Mobility in Germany (MiD) and the 2012 California Household Travel Survey (CHTS) provide an opportunity to start filling this gap by teasing out what built environment and socio-economic variables impact the likelihood that a household is carless (voluntarily or not) in Germany and in California, two car-dependent societies with different carless rates. Results from our generalized structural equation models show that in both Germany and California, households who reside in denser neighborhoods, closer to transit stations, and who have a lower income or fewer children, are more likely to be voluntarily carless. However, households with more education are more likely to be voluntarily carless in Germany, whereas the reverse is true in California. Moreover, employment density and public transit have a higher impact on voluntary carlessness in Germany than in California. Our results also show that different socio-economic groups have substantially different residential location preferences in Germany and in California. These differences may be explained by cultural preferences, historical differences in land use and transportation policies, and by the higher cost of owning a motor vehicle in Germany.